The Eucharistic Presence and Making Christ Present in the Word of God: A Study Inspired by the Views of Robert Sokolowski - Zatwardnicki, Sławomir (Collectanea Theologica, 2021)
Robert Sokolowski wrote that biblical words activate the presence of God. But can we speak of the “sacramentality of the word” analogous to the sacrament itself? This paper collects reflections on the “making present” of the word of God intra mysteriorum celebrationem. This issue is related to the theme of the relationship between past and present in the Eucharist, which was dealt with by Sokolowski. The article summarizes this philosopher’s views on the Eucharistic presence, in dialogue with which it then reflects on the presence of Christ in the word of God. From the “Passover-centricity” of the Holy Scriptures stems a kind of making present the anticipatory self-giving of God in the events to which the inspired texts testify. The liturgy of the word must lead to the climactic event of Passover and its sacramental making present. There can be no question of “two presences” of the Lord at Mass. The words of institution from the Last Supper have a role in the actualization of the Passover, while the inspired words are not in the same way “instituting” words. It is only in their inner orientation that they lead to the mystery of Christ present in the Blessed Sacrament.